2018
DOI: 10.1016/j.trsl.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic signatures to predict immune checkpoint blockade therapy response in patients with colorectal cancer

Abstract: Immune checkpoint blockade therapy (ICBT) has resulted in extended overall survival for some patients with certain types of cancer, most prominently including colorectal cancer (CRC) patients associated with microsatellite instability (MSI). However, most patients with CRC whose phenotypes have microsatellite stability (MSS) are unresponsive to ICBT. In efforts to understand the responsiveness of CRC tumors to ICBT, genotypic and phenotypic signatures of CRC tumors are now being investigated. The MSI and MSS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…The differentially expressed genes were mainly associated with pathways related to the immune and inflammatory responses, the major mechanisms involved in tumor response. Many studies demonstrated the close relationship between immune factors and survival of pancreatic, colorectal cancer, and GBM patients, [36][37][38][39] indicating the prognostic value of this sevengene signature. Together, this analysis extends previous data by using microdissection RNA-seq data to identify a necrosis gene set specifically in cancer tissue.…”
Section: Discussionmentioning
confidence: 93%
“…The differentially expressed genes were mainly associated with pathways related to the immune and inflammatory responses, the major mechanisms involved in tumor response. Many studies demonstrated the close relationship between immune factors and survival of pancreatic, colorectal cancer, and GBM patients, [36][37][38][39] indicating the prognostic value of this sevengene signature. Together, this analysis extends previous data by using microdissection RNA-seq data to identify a necrosis gene set specifically in cancer tissue.…”
Section: Discussionmentioning
confidence: 93%
“…After several trials, it became evident that almost all responders had the MSI subtype(Brahmer et al, 2010; Le et al, 2015). Although the mutational loads in different CRC subtypes are considered as one of the major determining factors of ICBT response(Zhao et al, 2018), other mechanisms regulating immune response are likely to exist. Indeed, around 40-70% of the immune infiltrated late stage MSI CRC with high mutational load failed in ICBT(Le et al, 2015; Oliveira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most CRC patients (>85%) have microsatellite stable (MSS) tumors(Kim et al, 2016; Mlecnik et al, 2016), that do not respond to ICBT. The MSI-H tumors are generally associated with a higher mutational load and are considered immunogenic(Salem et al, 2018; Zhao et al, 2018). Currently, the MSI/MSS phenotype is considered as a biomarker for ICBT response(Le et al, 2017; Mandal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…4A). In addition, the immune score, a method to assess the tumor immune microenvironment, has been shown to outperform the AJCC/UICC TNM classi cation in colorectal cancer (32,33). Furthermore, HMGCS2 expression was found to be negatively correlated with immune score in LUAD, COAD, COADREAD, KIRC, LIHC, BLCA, THCA, OV, TGCT, while positively correlated in LGG and MESO (Fig.…”
Section: Correlation Between Hmgcs2 Expression and The Tme In Differe...mentioning
confidence: 92%